Ethical Aspects of Some Related Concepts of Corporate Responsibility - Sruk, Vida; Ašanin Gole, Pedja (Mednarodno inovativno poslovanje = Journal of Innovative Business and Management, 2022)
The article discusses the concepts of corporate responsibility as a concept of applied ethics and connects philosophical and social science approaches and insights. The purpose of the article, based on the constructivist interpretative paradigm, is to investigate and confront some related concepts of corporate responsibility according to their normative content, namely according to the suitability of their use as a paradigmatic theory for business ethics. Thus, the concepts of corporate social responsibility, corporate social impact (or performance) and stakeholder theory are analyzed, which also leads to the analysis of key modern concepts such as corporate responsibility, accountability and corporate citizenship, which offer an important conceptual space for understanding business ethics beyond its traditional boundaries. It turned out that the weakness of the concept of social responsibility stems from the lack of its philosophical and ethical justification regarding when and under what conditions and in what way something is a moral subject.
Keywords: corporate responsibility; accountability; corporate social responsibility; corporate social performarce; corporate citizenship; sociology of responsibility; business ethics